Assessing the ASEAN Smart Cities Network (ASCN) via the Quintuple Helix Innovation Framework, with Special Regard to Smart City Discourse, Civil Participation, and Environmental Performance. Issue 1 (2nd January 2021) - Crumpton, Charles David; Wongthanavasu, Supawatanakorn; Kamnuansilpa, Peerasit; Draper, John; Bialobrzeski, Eva
ABSTRACT: The smart city movement (SCM) is spreading globally with increasing velocity. With its international allure, it has generated a burgeoning body of international literature, much of which forms what the current study refers to as a 'normalised discourse'. The international literature also includes a growing body of criticism that addresses hazards associated with this normalised discourse. The current study labels the collective product of this criticism as identification of the 'normalised problematics' of the SCM. In 2018, Singapore announced that 26 cities would form the ASEAN Smart Cities Network (ASCN). This article assesses the ASCN in terms of the SCM discourse and its normalised problematics through the Quintuple Helix frame of innovation economics. Our analysis suggests that the authoritarian nature of some ASEAN countries has serious implications for participatory and therefore socio-ecologically sustainable urban planning and governance, for the ASCN projects specifically, and for similar national and regional projects globally.